Proyecto de Inversión para la creación de una cancha sintética de indor-fútbol en la ciudad de Catacocha Provincia de Loja - Ríos Hurtado, Katherine Cecilia (2016)
The present investigation work was developed based on the general objective of carrying out a "investment Project for the creation of a synthetic court of indor-soccer in the city of Catacocha county of Loja", with the purpose of covering the necessity of this type of service like half of distraction for the childhood and youth of the city. For the realization of this project he/she left with the market study where 375 surveys were applied the inhabitants of the city of Catacocha with their respective statistical tabulation and analysis, being able to determine the demand and to know the existent offer in the town, being like unsatisfied demand for the first year of 33.770 annual services. In the technical study it was specified the operation and operability of the project like: size, localization and engineering, providing a work atmosphere for the good operation of the company. The entity for the first year established the capacity installed 4.615 annual services, what means 13,67% of attention to the market, also began with an used capacity of 90%; the systems and appropriate processes for the benefit of the service, the structural designs of the plant and the establishment of the human resources, materials and necessary financiers for the operation of the company, were determined in the engineering of the project. In the organizational study he/she is inmersa the Organizational and functional Structure, being a guide so that each one of the employees knows their responsibilities and carry out their functions correctly, for the handling and 6 administrative operation of the company exists a payroll of 4 people between directive and employees. By means of the economic study it was determined that the creation of the synthetic court has an investment of $87.513,37, that understands the work capital, of which $27.513,37 that it represents 31,44% will be financed with own capital, and $60.000,00 that 68,56% is equal it will be financed by a financial entity of the city; and whose period of recovery of invested capital will be in 3 years, 1 month and 2 days, demonstrating in this way that in the first year of life of the project a net utility of the exercise of $23.706,49 will be obtained. Finally in the Financial Evaluation it was analyzed the different financial indicators that allowed to establish the viability of the project like they are: Net Current value (they GO) of $21.244,48; it Appraises it Interns of Return (TIR) of 18,99%; and Relationship Benefits Cost (RBC) $1,00; Analysis of Sensibility with Increment of the Costs of 33,72% obtaining a sensibility of the 0,99; and with a Decrease in the Revenues of 16,82% obtaining a sensibility of 0.99, what means that in spite of these changes the project is not sensitive and it can resist this changes; the same ones that demonstrate the feasibility of the project to implant the synthetic court in the city of Catacocha. For it you can conclude that after the realization of the market study it has been determined that a great demand exists willing to receive the service of rent of a synthetic court in the city of Catacocha, due to the great acceptance demonstrated 7 in the investigative study, where its execution is recommended since it generates good revenues and therefore he/she would help to the growth and economic progress of the city.